Living hydrogel with blood derived elements for wound healing - Yuanyuan Jiang; Xiangyi Wu; Xiaoju Wang; Bin Kong; Jinglin Wang; Hongbo Zhang (Materials Today Bio)
Blood plays a vital role in wound healing, as platelets (PLTs) initiate primary hemostasis and red blood cells (RBCs) continuously supply oxygen. Inspired by the intrinsic functions of RBCs and PLTs, we developed a living hydrogel incorporating RBCs, PLTs, and black phosphorus quantum dots (BP QDs) to accelerate wound healing. Owing to its three-dimensional (3D) pleated surface structure and excellent biocompatibility, the hydrogel exhibited enhanced cell seeding efficiency and provided effective support for both hemostasis and tissue regeneration. By leveraging the photo-responsive properties of BP QDs, the hydrogel acquired a controllable photothermal effect, enabling NIR-triggered oxygen release. Additionally, polymyxin was incorporated into the hydrogel matrix to endow the material with antibacterial properties. Benefiting from these combined features, the bioinspired living hydrogel significantly promoted wound repair in in vivo evaluations. Collectively, these findings highlight the potential of our bioinspired living hydrogel as a promising therapeutic strategy for enhanced wound healing.